Exogenous diethyl aminoethyl hexanoate alleviates the damage caused by low-temperature stress in Phaseolus vulgaris L. seedlings through photosynthetic and antioxidant systems - Yu Bai; Qiya Dai; Yanheng He; Li Yan; Jianpo Niu; Xuan Wang; Yongdong Xie; Xuena Yu; Wen Tang; Huanxiu Li; Zhi Huang; Bo Sun; et al. (BMC Plant Biology)
Abstract Background Phaseolus vulgaris is a warm-season crop sensitive to low temperatures, which can adversely affect its growth, yield, and market value. Exogenous growth regulators, such as diethyl aminoethyl hexanoate (DA-6), have shown potential in alleviating stress caused by adverse environmental conditions. However, the effects that DA-6 has on P. vulgaris plants subjected to low-temperature stress are not well understood. This study aimed to investigate the impact DA-6 has on the growth, photosynthesis, antioxidant system, and gene expression in cold-tolerant (YJ009763) and cold-sensitive (Baibulao) P. vulgaris seedlings under low-temperature stress. Results To simulate low-temperature stress, P. vulgaris seedlings were exposed to 5 °C, and 25 mg/L DA-6 solution applied to their leaves. This study revealed that DA-6 significantly enhanced the growth and photosynthetic performance of P. vulgaris seedlings under low-temperature stress. Specifically, DA-6 increased chlorophyll content and photosynthetic rates, reducing stomatal limitation and enhancing carbon assimilation. It also improved the photosynthetic efficiency by boosting electron transport in the reaction center. The antioxidant enzyme activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) were markedly increased following DA-6 treatment. After 24 h of low-temperature stress, the cold-tolerant seedlings showed a 68.95% increase in POD activity, whereas the cold-sensitive seedlings displayed a 160.63% increase in SOD activity and an 85.56% increase in CAT activity. In addition, DA-6 significantly reduced the production rate of superoxide anion radical generation, with a 25.24% reduction in cold-tolerant seedlings and a 49.38% reduction in cold-sensitive seedlings. Under low-temperature stress, exogenous DA-6 could upregulate the relative expression of antioxidant enzyme-related genes, such as PvSOD and PvAPX. DA-6 also promoted the expression of key antioxidant genes, including PvMDHAR and PvDHAR2, which accelerated the ascorbate-glutathione cycle and mitigated oxidative stress. Conclusion Exogenous application of DA-6 effectively alleviates low-temperature stress in P. vulgaris by enhancing photosynthetic capacity and regulating the antioxidant defense system. Cold-tolerant varieties exhibited a stronger response to DA-6, demonstrating a greater ability to withstand cold stress. These findings suggest that DA-6 treatment could serve as a promising approach for improving the resilience of P. vulgaris to low temperatures.